2014
DOI: 10.1371/journal.pone.0087124
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Dysfunction Underlies the Development of the Split-Hand in Amyotrophic Lateral Sclerosis

Abstract: The split-hand phenomenon, a specific feature of amyotrophic lateral sclerosis (ALS), refers to preferential wasting of abductor pollicis brevis (APB) and first dorsal interosseous (FDI) with relative preservation of abductor digiti minimi (ADM). The pathophysiological mechanisms underlying the split-hand phenomenon remain elusive and resolution of this issue would provide unique insights into ALS pathophysiology. Consequently, the present study dissected out the relative contribution of cortical and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 50 publications
3
67
0
Order By: Relevance
“…The concept that the disease process can be primarily influenced by the cerebral cortex is corroborated by the clinical findings reported for split-hand syndrome and split-leg phenomenon [48][49][50][51][52][53][54]. Clinical sALS phenotypes that eventually allow for alternative interpretations, e. g., flail-arm or flail-leg syndrome [45][46][47]55], still require neuropathological confirmation [56,57].…”
Section: Discussionmentioning
confidence: 90%
“…The concept that the disease process can be primarily influenced by the cerebral cortex is corroborated by the clinical findings reported for split-hand syndrome and split-leg phenomenon [48][49][50][51][52][53][54]. Clinical sALS phenotypes that eventually allow for alternative interpretations, e. g., flail-arm or flail-leg syndrome [45][46][47]55], still require neuropathological confirmation [56,57].…”
Section: Discussionmentioning
confidence: 90%
“…The pathophysiological mechanism of this phenomenon in ALS is uncertain. A cortical‐based process related to a larger representation of the thenar muscles has been proposed . Menon et al .…”
mentioning
confidence: 99%
“…A cortical-based process related to a larger representation of the thenar muscles has been proposed. 2 Menon et al 2 reported that short interval intracortical inhibition, a biomarker of cortical excitability, was significantly reduced in the abductor pollicis brevis (APB), first dorsal interosseous (FDI), and ADM muscles in patients with ALS, although the reduction was most pronounced when recorded over APB/FDI muscles. Moreover, in a study that evaluated the cortical/peripheral stimulation evoked response (motor evoked potential/compound muscle action potential [CMAP]) ratios, Weber at al.…”
mentioning
confidence: 99%
“…It is recognized that excitability of different nerves is heterogeneous, as suggested by the 'split hand' syndrome in amyotrophic lateral sclerosis (Eisen & Kuwabara, 2012), although reflecting a primarily cortical dysfunction (Menon et al, 2014). This indicates that intrinsic functional differences of motor axons in the ulnar and median nerves could influence their response during pathological situations.…”
Section: Modeling Of Myelinated Axonsmentioning
confidence: 99%